On the Study of an Initial Value Problem for a Second Order Differential Equation Set in a Singular Cylindrical Domain - Belkacem, Chaouchi; Kostic, Marko (Sarajevo Journal of Mathematics, 2022)
We will investigate an initial value problem for a second order differential equation set in a singular cylindrical domain $Π $. The existence, uniqueness and maximal regularity results are obtained for the classical solutions by using the semigroup theory. The study is performed in the framework of little Hölder space $h^{2σ }(Π )$ with $0<2σ <1$.